Magnetoliposomes with calcium-doped magnesium ferrites anchored in the lipid surface for enhanced DOX release - Cardoso, Beatriz Dias (2023)
Nanotechnology has provided a new insight into cancer treatment by enabling the development of nanocarriers for the encapsulation, transport, and controlled release of antitumor drugs at the target site. Among these nanocarriers, magnetic nanosystems have gained prominence. This work presents the design, development, and characterization of magnetoliposomes (MLs), wherein superparamagnetic nanoparticles are coupled to the lipid surface. For this purpose, dimercaptosuccinic acid (DMSA)-functionalized Ca0.25Mg0.75Fe2O4 superparamagnetic nanoparticles were prepared for the first time. The magnetic nanoparticles demonstrated a cubic shape with an average size of 13.36 nm. Furthermore, their potential for photothermal hyperthermia was evaluated using 4 mg/mL, 2 mg/mL, and 1 mg/mL concentrations of NPs@DMSA, which demonstrated a maximum temperature variation of 20.4 °C, 11.4 °C, and 7.3 °C, respectively, during a 30 min NIR-laser irradiation. Subsequently, these nanoparticles were coupled to the lipid surface of DPPC/DSPC/CHEMS and DPPC/DSPC/CHEMS/DSPE-PEG-based MLs using a new synthesis methodology, exhibiting average sizes of 153 ± 8 nm and 136 ± 2 nm, respectively. Doxorubicin (DOX) was encapsulated with high efficiency, achieving 96% ± 2% encapsulation in non-PEGylated MLs and 98.0% ± 0.6% in stealth MLs. Finally, drug release assays of the DOX-loaded DPPC/DSPC/CHEMS MLs were performed under different conditions of temperature (37 °C and 42 °C) and pH (5.5 and 7.4), simulating physiological and therapeutic conditions. The results revealed a higher release rate at 42 °C and acidic pH. Release rates significantly increased when introducing the stimulus of laser-induced photothermal hyperthermia at 808 nm (1 W/cm2) for 5 min. After 48 h of testing, at pH 5.5, 67.5% ± 0.5% of DOX was released, while at pH 7.4, only a modest release of 27.0% ± 0.1% was achieved. The results demonstrate the potential of the MLs developed in this work to the controlled release of DOX under NIR-laser stimulation and acidic environments and to maintain a sustained and reduced release profile in physiological environments with pH 7.4.